2015
DOI: 10.2500/ar.2015.6.0119
|View full text |Cite
|
Sign up to set email alerts
|

Monitor Height Ergonomics: A Comparison of Operating Room Video Display Terminals

Abstract: A surgeon's eyes should be positioned 1 meter (m) distant and no more than 15° below the top of an operating monitor (0.27 m). We sought to determine which operating room video display terminal can best accommodate ergonomically optimized gaze during surgery. Floor to eye height was measured for surgeons in seated, perched, and standing positions. These ranges were then compared to vertical displacement ranges for monitors measured from floor to top of the screen. Eye height was measured for standing (1.56–1.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Because surgical performance can be influenced by the surgeon’s comfort, heads-up surgery helps to enhance the procedure’s safety. Using TM, the vitreoretinal surgeon cannot move the head, shoulders and back during the operation, and neck and musculoskeletal fatigue, stiffness, mental and physical stress, and eyestrain are commonly reported after surgery [ 7 ]. The 3DM procedure is more comfortable because the surgeon can choose the most comfortable surgical position that allows some degree of movement [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because surgical performance can be influenced by the surgeon’s comfort, heads-up surgery helps to enhance the procedure’s safety. Using TM, the vitreoretinal surgeon cannot move the head, shoulders and back during the operation, and neck and musculoskeletal fatigue, stiffness, mental and physical stress, and eyestrain are commonly reported after surgery [ 7 ]. The 3DM procedure is more comfortable because the surgeon can choose the most comfortable surgical position that allows some degree of movement [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main laparoscopic console should be in direct view of the surgeon or assistant to prevent rotation or poor posture to visualize equipment settings. 24,58 The monitor height should be in front of the operator and approximately 10 to 25 degrees below the horizontal plane of the eye with a downward gaze (►Fig. 1).…”
Section: Laparoscopymentioning
confidence: 99%
“…Among ergonomic-related issues for surgeons, surgical table height, mayo stand height, and monitor position are key concerns, where the latter is the most significant factor impacting surgeon work performance and satisfaction (Marcos, Seitz, Bubb, Wichert, & Feussner, 2006; Matern & Koneczny, 2007). Through an ergonomic analysis of different screen configurations, Kelts, McMains, Chen, and Weitzel (2015) found that ceiling mounted booms provided the most flexible range of heights and were able to accommodate the ergonomic requirements for the surgeons in standing and perched positions as well as seating positions for tall surgeons (Kelts, McMains, Chen, & Weitzel, 2015). Additionally, positioning the monitor at eye-level reduced neck muscle strain among surgeons (Kelts et al, 2015).…”
Section: Methodsmentioning
confidence: 99%